2022
DOI: 10.1038/s43856-022-00195-4
|View full text |Cite
|
Sign up to set email alerts
|

Early SARS-CoV-2 dynamics and immune responses in unvaccinated participants of an intensely sampled longitudinal surveillance study

Abstract: Background A comprehensive understanding of the SARS-CoV-2 infection dynamics and the ensuing host immune responses is needed to explain the pathogenesis as it relates to viral transmission. Knowledge gaps exist surrounding SARS-CoV-2 in vivo kinetics, particularly in the earliest stages after exposure. Methods An ongoing, workplace clinical surveillance study was used to intensely sample a small cohort longitudinally. Nine study participants who d… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
5
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 38 publications
1
5
1
Order By: Relevance
“…It has been suggested that amplification and detection of the short sequences targeted by primers used in the clinical RT-qPCR tests may measure SARS-CoV-2 RNA fragments rather than infectious virus, thereby biasing the length of the observed clearance phase. Our results contradict this rationale, because we previously measured SARS-CoV-2 RNA in COVID-19 patients for up to 90 days ( 2 ), while the time from C max to undetectable was less than 1 week in the current study using the same methods.…”
Section: Observationcontrasting
confidence: 88%
See 4 more Smart Citations
“…It has been suggested that amplification and detection of the short sequences targeted by primers used in the clinical RT-qPCR tests may measure SARS-CoV-2 RNA fragments rather than infectious virus, thereby biasing the length of the observed clearance phase. Our results contradict this rationale, because we previously measured SARS-CoV-2 RNA in COVID-19 patients for up to 90 days ( 2 ), while the time from C max to undetectable was less than 1 week in the current study using the same methods.…”
Section: Observationcontrasting
confidence: 88%
“…The t d and C max values were comparable to those observed in our previous study ( 2 ) ( Fig. 1G ), but the clearance phase was much shorter, with both participants being SARS-CoV-2 RNA positive for less than 2 weeks ( Fig.…”
Section: Observationsupporting
confidence: 86%
See 3 more Smart Citations